2019
DOI: 10.31086/tjgeri.2019.100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fibrinogen -to- albumin ratio and angiographic no-reflow in elderly patients with st-elevation myocardial infarction treated with primary percutaneous coronary intervention

Abstract: Introduction: Primary percutaneous coronary intervention carries a low success rate and high procedural risk in elderly patients. No-reflow is a serious complication of primary percutaneous coronary intervention in the treatment of acute ST-elevation myocardial infarction. We evaluated whether admission fibrinogen-to-albumin ratio, which has emerged as an inflammatory and haemorheological marker for predicting adverse outcomes in some cardiovascular diseases, predicts angiographic no-reflow in elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…performed a study of 617 STEMI patients, who underwent PCI in older adults with median age of 75 years old and found that increased level of FAR was higher in the no‐reflow group compared to the normal flow group. 10 The no‐flow group was determined based on thrombolysis in myocardial infarction (TIMI) flow grades and TIMI < 3 in all these studies. 5 , 8 , 10 Until now, revascularization has been examined as a secondary endpoint with a very small pool of patients.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…performed a study of 617 STEMI patients, who underwent PCI in older adults with median age of 75 years old and found that increased level of FAR was higher in the no‐reflow group compared to the normal flow group. 10 The no‐flow group was determined based on thrombolysis in myocardial infarction (TIMI) flow grades and TIMI < 3 in all these studies. 5 , 8 , 10 Until now, revascularization has been examined as a secondary endpoint with a very small pool of patients.…”
Section: Figurementioning
confidence: 99%
“… 10 The no‐flow group was determined based on thrombolysis in myocardial infarction (TIMI) flow grades and TIMI < 3 in all these studies. 5 , 8 , 10 Until now, revascularization has been examined as a secondary endpoint with a very small pool of patients. Overall, this meta‐analysis showed high FAR group may have a higher risk of requiring emergent‐unscheduled revascularization.…”
Section: Figurementioning
confidence: 99%